KARAKTER MANUSIA DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Saputra, Anri; Usiono, Usiono; Siregar, Pamonoran (Jurnal Bilqolam Pendidikan Islam, 2024)
Understanding human character in Islam plays an important role in supporting the success of Islamic education. This education is realized through a deep understanding of the concept of learners, the duties of educators, the formulation of objectives, and a curriculum that is in accordance with Islamic values. In addition, the use of appropriate learning methods at each stage of student development, both physically and spiritually, as well as the implementation of evaluations that are oriented towards the development of human potential are also important aspects. All of these efforts aim to always remind humans that Allah is the ultimate goal of life. This study aims to examine human character from the perspective of Islamic educational philosophy. With a library research approach, this study analyzes various thoughts of Muslim philosophers, both classical and contemporary, regarding human character. The results of the study show that in Islam, human character has complex dimensions, including physical, spiritual, social, and intellectual aspects. Human character is not only seen as an individual entity, but also as a social being who is responsible for the environment and society. The implication of this study is the importance of Islamic education in developing all human potential as a caliph (leader) on earth. Islamic education does not only aim to create knowledgeable individuals, but also to shape human character that is able to carry out its role and responsibilities in the world, in accordance with divine values ​​that will bring them back to Allah as the ultimate goal.